Common and Divergent Immune Response Signaling Pathways Discovered in Peripheral Blood Mononuclear Cell Gene Expression Patterns in Presymptomatic and Clinically Apparent Malaria - Ockenhouse, Christian F; Hu, Wan-chung; Kester, Kent E; Cummings, James F; Stewart, Ann; Heppner, D. Gray; Jedlicka, Anne E; Scott, Alan L; Wolfe, Nathan D; Vahey, Maryanne; Burke, Donald S (Infection and Immunity, 2006)
Using genome-wide expression profiles from persons either experimentally challenged with malaria-infected mosquitoes or naturally infected with Plasmodium falciparum malaria, we present details of the transcriptional changes that occur with infection and that either are commonly shared between subjects with presymptomatic and clinically apparent malaria or distinguish these two groups. Toll-like receptor signaling through NF-κB pathways was significantly upregulated in both groups, as were downstream genes that function in phagocytosis and inflammation, including the cytokines tumor necrosis factor alpha, gamma interferon (IFN-γ), and interleukin-1β (IL-1β). The molecular program derived from these signatures illuminates the closely orchestrated interactions that regulate gene expression by transcription factors such as IRF-1 in the IFN-γ signal transduction pathway. Modulation of transcripts in heat shock and glycolytic enzyme genes paralleled the intensity of infection. Major histocompatibility complex class I molecules and genes involved in class II antigen presentation are significantly induced in 90% of malaria-infected persons regardless of group. Differences between early presymptomatic infection and natural infection involved genes that regulate the induction of apoptosis through mitogen-activated protein (MAP) kinases and signaling pathways through the endogenous pyrogen IL-1β, a major inducer of fever. The induction of apoptosis in peripheral blood mononuclear cells from patients with naturally acquired infection impacted the mitochondrial control of apoptosis and the activation of MAP kinase pathways centered around MAPK14 (p38α and p38β). Our findings confirm and extend findings regarding aspects of the earliest responses to malaria infection at the molecular level, which may be informative in elucidating how innate and adaptive immune responses may be modulated in different stages of infection.